ESTIMATION OF ND:YAG LASER ENERGY FOR VARIOUS TYPES OF POSTERIOR CAPSULE OPACITY: Oral Presentation - Observational Study - Resident - INTAN EKARULITA; Andrew M. H. Knoch; Feti Karfiati; Ludwig Melino Tjokrovonco; Emmy Dwi Sugiarti; Budiman (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Types of Posterior capsule opacity (PCO) are membranous, fibrotic, or fibro-membranous. Surgical capsulotomy has been replaced by Neodymium-doped Ytrium Aluminim Garnet (Nd:YAG) as a PCO management nowdays. The initial energy use of the laser is influenced by variations in PCO density. Utilizing initial energy effectively can help to use less total laser energy. This study is to estimate energy Nd:YAG laser levels to treat various types of PCO. Methods : This is a observational descriptive study with cross-sectional design. This study retrieved initial and total capsulotomy Nd:YAG laser as a main variable on various types of PCO. The best corrected visual acuity (BCVA) before and after laser, size of hole capsulotomy, and complications of each type of PCO were evaluated. Results : A total 59 eyes of 49 patients with pseudophakia who underwent capsulotomy laser were included. The mean values of initial energy levels were 1,45±0,31 mJ for membranous PCO, 1,51±0,29 mJ for fibrous PCO, and 1,68±0,23 mJ for fibro-membran PCO. The mean summated energy levels for membranous PCO was 51,86±28,19 mJ, 78,86±44,81 mJ for fibrous PCO, 86,88±60,51 mJ for fibro- membran PCO. Complications were iritis, oculi hypertension, hyaloid rupture and IOL pitting were occurred in this study. Conclusion : Fibro-membran PCO required more initial and total laser energy compared to membranous and fibrous PCO